First Book of Quantum Field Theory - Lahiri, Amitabha; Pal, Palash B. (New Delhi: Narosa Publishing House, 2005)
This book introduces QFT for a reader with no prior knowledge of the subject. It is meant to be a textbook for advanced undergraduate or beginning postgraduate students. The book discusses quantization of fields, S-matrix theory, Feynman diagrams, calculation of decay rates and cross sections, renormalization, symmetries and symmetry breaking. Some background material on classical field theory and group theory, needed for the exposition, are also presented in the book. Detailed calculations of weak and electromagnetic processes are included. There are many exercise problems to help the students, instructors and beginning researchers in the field.The second edition improves upon some notations and explanations, and includes answers to selected exercises.
Index 373-380p.
Keywords: Quantization; Quantum electrodynamics; Renormalization; Preliminaries